2021
DOI: 10.2298/gensr2103219p
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distance of maize inbreds for prediction of heterosis and combining ability

Abstract: A panel of seven maize inbred lines belonging to Zemun Polje commercial pool were genotypized using SNPs bead chip. 21 hybrids, developed according to the half dialel mating design, were tested in the field together with inbred lines per se. The goal of the study was to determine the genetic distance among seven maize inbred lines and to establish whether there was a significant correlation between the genetic distance among parental inbreds and grain yield, specific combining abilities (SCA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Research has shown that high-yielding hybrid varieties possess several superior alleles, indicating the importance of genetic distance between parental inbred lines (Huang et al, 2015). Furthermore, the genetic distance between inbred lines has been demonstrated to be predictive of heterosis and combining ability in maize, with more genetically distant inbred lines showing higher potential for heterosis (Perić et al, 2021). This is supported by the finding that hybrids derived from inbred lines with high genetic distance exhibit low seed yield, emphasizing the significance of genetic distance in hybrid performance (Fareghi et al, 2019).…”
Section: Figure 1 Heatmap Data Of Correlationmentioning
confidence: 99%
“…Research has shown that high-yielding hybrid varieties possess several superior alleles, indicating the importance of genetic distance between parental inbred lines (Huang et al, 2015). Furthermore, the genetic distance between inbred lines has been demonstrated to be predictive of heterosis and combining ability in maize, with more genetically distant inbred lines showing higher potential for heterosis (Perić et al, 2021). This is supported by the finding that hybrids derived from inbred lines with high genetic distance exhibit low seed yield, emphasizing the significance of genetic distance in hybrid performance (Fareghi et al, 2019).…”
Section: Figure 1 Heatmap Data Of Correlationmentioning
confidence: 99%
“…Meteorological conditions are highly variable and unpredictable and greatly affect stability and yield (POPOVIĆ et al, 2012;JANKOVIĆ et al, 2018;LAKIĆ et al, 2019;TERZIĆ et al, 2019;POPOVIĆ et al, 2020a;2020b;JOVANOVIĆ-TODOROVIĆ et al, 2020;PERIĆ et al, 2021). The data of the Republic Hydrometeorological Institute of the Republic of Srpska was used for the analysis of weather conditions.…”
Section: Meteorological Conditionsmentioning
confidence: 99%